HUBUNGAN ANTARA KELINCAHAN DAN KECEPATAN TERHADAP KETERAMPILAN HASIL MENGGIRING BOLA PADA CLUB FUTSAL SMA NEGERI 1 KAMPAR UTARA - Ananda, Indalas; Zainur, Zainur; Sulastio, Agus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this research is that the dribbling dexterity doesn't look optimal, which is demonstrated by the dribbling students. So that the ball being controlled tends to be taken by the opponent. The aim of this research was to determine the relationship between agility and speed with dribbling. SMA Negeri 1 Kampar Utara, with a total of 20 subjects, used a total sampling technique. The instruments in this research were the shuttle run, the 60 meter run and the dribble test. The data obtained was analyzed using the product moment correlation. Based on the normality test analysis of the data, X1 produces Lcount of 0.116 and Ltable of 0.190 and X2 produces Lcount of 0.142 and Ltable of 0.190. while the variable Y produces Lcount of 0.160 and Ltable of 0.190. This means Lcount < LTable. Based on statistical data analysis, the data is normally distributed. Based on the above analysis requirement test, the hypothesis test on the X1 and X2 variables on the Y variable data is 0.901 > 0.456 Rcount > R table data. Thus, there is a common relationship between agility and speed on the skills resulting from dribbling on the futsal club of SMA Negeri 1 North Kampar. Key Words: Agility, Speed, Dribbling Skills